PENGARUH STRES KERJA TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN PADA KARYAWAN DI PT PANIN BANK BANJARMASIN - Toman Romanco Sormin; Hastin Umi Anisah; Maya Sari Dewi (JWM (JURNAL WAWASAN MANAJEMEN), 2017)
This study aimed to identif and analyze the influence of Works Stress (X1) as independen variable and Job satisfaction (Z) as intervening variable either employee performance (Y) as the dependent variable on the employee off PT Panin Bank Banjarmasin TBK.This was explanatory research with unit analysis of PT Panin Bank Banjarmasin. The sampling technique used in study was stratified sampling with 102 employee. Measurement of variables is done by using likert scale technique with weight scale from 1 to 5. Path Analysis were used to analyze the effect of work stress among variables (X1) and Job Satisfaction (Z) on employee performance (Y). Furthermore, to test the level of significance with SPSS version 22 used. The study concluded that two independent variables simultaneously, namely work stress (X1) with job Satisfaction variables (Z) have significant relationship to employee performance (Y). Meanwhile, individually, job satisfaction variable (Z) has significant positive relationship on employee performance (Y).